Breast cancer treatment-associated cardiovascular toxicity and effects of exercise countermeasures. Issue 1 (December 2016) - Yu, Anthony; Jones, Lee
Abstract Advances in breast cancer treatment have improved disease-free survival and overall survival in women with early-stage breast cancer. However, these improvements may be attenuated by the adverse cardiovascular effects associated with breast cancer adjuvant therapy. Exercise may be a potential strategy to counteract these toxicities. The purpose of this paper is to provide an overview on the adverse cardiovascular effects of breast cancer therapy as well as the evidence supporting the potential cardioprotective effects of exercise training in breast cancer patients during and after treatment. We will also discuss research gaps and avenues for future research.